Desire to learn qualitative methods among researchers in healthcare fields - Warren Bareiss (Qualitative Research in Medicine & Healthcare, 2023)
July 2023 saw the high point to date of my 25+ years in academe. I had the pleasure of presenting a workshop—“ Strategies for Writing Effective Qualitative Research in Healthcare”—at the 18th annual conference of the International Society for the Study of Self-Injury (NSSI). Hosted by the Medical University of Vienna, the conference featured dozens of presentations, of which a sizeable minority were qualitative in nature. Qualitative research at the conference addressed such topics as stigma pertaining to NSSI, young adults’ experiences with NSSI in India, healthcare staff views of NSSI behaviors, and reasoning/beliefs among patients who self-injure [...]